Implementación de una aplicación multiplataforma para control, venta y gestión de publicidad mediante web semántica en la Asociación Autónoma de Carpintería en Aluminio & Vidrios del cantón La Maná. - Chugchilan Baraja, Mario Olimpo (2021)
This research deals with the implementation of a multiplatform application in which the Autonomous Association of Aluminum and Glass Carpentry of canton La Maná can control its products, sell through the application and also can manage the advertising of its products in order to automate internal processes such as control, sales and external processes such as advertising management, having more scope to promote what they manufacture to the population of the canton, as potential customers, which would mean an improvement in the marketing of their products. In addition, the implementation of this application indirectly benefits the population of the canton by making an application available to them that allows them to see what they manufacture in the association and to place online orders for any product they require, having the freedom to place the order from the place where they are without the need to go to the manufacturing site. This project was developed under the framework of the Scrum methodology applying its phases for development, collecting requirements, the structure of the multiplatform application, the development is executed under the framework of development tools such as JavaScript, PHP, Symfony, Bootstrap and for the storage of the information that will be registered in the application, the MySQL database management system was used as the last of the phases, tests were carried out on the application already implemented in the presence of the client to verify the quality of the software if it complies with the parameters requested by the client and if it can already be used by users. Once the phases of the Scrum methodology have been executed, training on the use and management of the system is carried out for him or the people in charge of the administration of the application.